PERAN SERTA KONSUMEN DAN PELAKU USAHA DALAM MEWUJUDKAN PERLINDUI\GAN KONSUMEN (Dinamika Ekonomi, 2003)
In the Indonesia rule of law, the concept of "Consumen" had been introducedsince the rule no 8 of 1999 published about the protection for the customer.In order toprotect the customer, the role of the customer and the businessman is very important.The customer is the determiner in whether to buy certain product or not. Meanwhile thebusinessman as the person who produce thing or service need to get.the highest profit sothat he will forget to consider the customer's right. The businessman should alsoconsider the customer's satisfaction and thing he produced will be qualified asstandardized. This condition seems to become the contradictory needs. The customer'sright must be protected and the producer's right is achieving the higher profit. In factbetween the customer and producer should not be contradictory bui through thecostumer's satisfaction the producer may gain their profit. This condition will achive theprotection for the customer.